Multifunctional walnut picking device - WANG XIUFEN; ZHAO YONG (2016)
The invention relates to a walnut picking tool, in particular to a multifunctional walnut picking device. The multifunctional walnut picking device comprises a picking rod, the bottom of the picking rod is provided with a control switch, the middle of the picking rod is provided with a control unit, and the control unit is connected with a solar battery panel and a storage battery separately; the top of the picking rod is provided with scissors, and a collecting device is arranged under scissor edges. According to the multifunctional walnut picking device, double power supplies including the solar battery panel and the storage battery are adopted, the scissor actions are controlled by the control switch, the whole device is compact in structure and can be operated by a single person, the labor intensity of picking personnel is reduced, and the conventional requirements such as fruit thinning and flower thinning in fruit tree management can be met. 本发明涉及核桃采摘工具，具体是种多功能核桃采摘器，包括采摘杆，采摘杆的底部设有控制开关，采摘杆中部设有控制单元，所述的控制单